Predictors of Customer Loyalty in the Malaysian Hotels' Outsourcing Relationships - Maria Abdul Rahman; Yusniza Kamarulzaman (International Review of Management and Marketing, 2016)
The success of a firm in an outsourcing relationship depends on the loyalty of a business customer towards its service providers. Therefore, it is crucial for service providers to focus on relationship marketing strategies to increase their customers' loyalty. However, there is little agreement as to which relationship marketing strategies that should be used to maintain customer loyalty. This study intends to examine the relationships between relational norms, relationship quality, and customer loyalty. Data collected from 159 hotel managers were analyzed using Partial Least Squares. Results of this study revealed that relational norms and relationship quality are positively related to customer loyalty.